Mangosteen (Garcinia mangostana L.) Rind Extract Lip Balm Formulation and Evaluation - Feronika Evma Rahayu; Sofa Rahmah; Dharma Yanti; Lia Warti (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2025)
Research on lip balm was conducted to determine how the formulation affected its characterization and stability when containing mangosteen rind extract. Thin-layer chromatography, microscopy, and phytochemical screening procedures were used to evaluate mangosteen rind extract. The freeze-thaw technique was used to create the lip balm formulation and to test its stability. The yield of coccal crystals made from mangosteen rind extract, which had an Rf value of 0.39, was 11.37% w/w. The concentration of the extract in the form of F0 (blank), F1 (2.5%), F2 (5%), F3 (7.5%), and F4 (10%) was varied to create lip balm compositions. The ingredients are combined into a base that has already been adjusted to create lip balm. Evaluations of lip balm preparations were conducted using organoleptic tests, homogeneity tests, pH tests, melting point tests, spreadability tests, centrifugation tests, and freeze-and-thaw tests. The results of the physical characteristics of the lip balm preparation were good and met the requirements based on the organoleptic test, homogeneity test, pH test, melting point test, and spreadability test. The stability test showed that the lip balm preparation was physically stable, with no change after 6 cycles. The normality test shows a p-value > 0.05, indicating that the formulation is normally distributed. Homogeneity test >0.05, which means there is no significant difference between the formulas. The one-way ANOVA test shows p < 0.05, indicating an effect on the pH of all formulas.